Low hemoglobin A1c levels in a patient with diabetic ketoacidosis: Fulminant type 1 diabetes mellitus - Keskin, Melikşah; Savaş-Erdeve, Şenay; Çetinkaya, Semra; Aycan, Zehra (The Turkish Journal of Pediatrics, 2018)
Fulminant type 1 diabetes mellitus (FT1DM) is a clinical condition that is characterized by remarkably rapid and complete pancreatic β-cell destruction, rapid onset of hyperglycemic symptoms followed by ketoacidosis. In most cases this process takes a few days. Although rare, there have been clinical manifestations with a prolonged progress that lasts longer than one week. This study focused on the case of a 35-monthold boy who was referred to our clinic with the diagnosis of diabetic ketoacidosis, and later had a modest elevation in hemoglobin A1c (HbA1c) levels (6.7 %) incompatible with his significantly elevated blood glucose levels. The autoantibodies against pancreatic β-cells were negative. On the basis of these above mentioned findings, our patient was then diagnosed with fulminant type 1 diabetes mellitus. If patients with diabetic ketoacidosis have no elevation in HbA1c levels, they should be assessed for possible clinical factors that can lead to lower detectable levels of HbA1c. Furthermore, FT1DM which is characterized by very rapid and potentially fatal progression should be considered as a differential diagnosis in these patients.
Keywords: childhood; diabetic ketoacidosis; insulin dependent diabetes mellitus